Inspeksi Kesehatan Lingkungan Di Sekolah Menengah Pertama Negeri 2 Dramaga Kabupaten Bogor Jawa Barat Tahun 2022 - Indah Restiaty Nazir; Maudina Alifia Afifah; Rojali Rojali (Jurnal Sehat Mandiri, 2022)
One of the factors that can affect the learning process and the health of school residents is the hygiene of the school environment. A potentially disease-causing school environment necessitates a school environmental health inspection to maintain a healthy school environment and promote students' clean and healthy lifestyles. This study seeks to characterize the health status of the school environment at State Junior High School 2 Dramaga in Bogor, West Java. This study is an observational descriptive study. The scope of the study includes the health of the school environment, including location, building construction, building space, room air quality, lighting, ventilation, school sanitation facilities, sports facilities, worship facilities, the yard, and the absence of mosquito larvae. Observation with a checklist and measurements of the physical environment, including classroom density, lighting, and ventilation measurements, were used to collect data. The results indicated positively to the health of the school environment. Efforts to improve school sanitation in the regulation and coaching sections yielded positive results. However, in terms of building space, lighting, toilets, and the absence of mosquito larvae, and the results are not favorable. The research findings on the health of the school environment led to a positive conclusion with a percentage of 69.2%. In addition to advising schools on how to enhance their facilities and infrastructure, researchers also monitor the schools' environmental health.